Interaction of environment conditions and genotypes on expression of genetic background in micro-phenophases of strawberry mixed flower bud. - Ana Selamovska, S. Kratovalieva, K. Nikolic (GENETIKA, 2013)
The aim of this research is differentiation of microphenophases of reproductive organs on two junebearing strawberry (Fragaria x anannassa) varieties senga sengana and pocahontas, depending on climate conditions, rosettes ordering and cultivate manner (orchard mulched on black foil and orchard on bare soil). The beginning of differentiation of flower buds is genetic characteristic depending on climate conditions (insulations, day length, higher the sum of rainfalls from the beginning of May until the end of July), order of rosettes and cultivate manner. The sum of effective temperatures over 10oC from 1st of May till the beginning of differentiation has no influence on beginning of flower buds differentiation. First morphological changes of the apical meristem were started in the first decade of August that has coincided with the day length of 14 hours and day insulations of 9.3 hours. Micro-phenophases were undergoing almost at the same time in both varieties, only the beginning at pocahontas was 2-3 days earlier. Primary rosettes differ 10-15 days earlier than secondary rosettes. Plants that grown on black foil had 7-10 days earlier flower bud differentiation compared to those grown on bare soil.
Keywords: strawberry, mixed flower buds, differentiation, microphenophases